The role of hippocampal glutamate receptor-A-dependent synaptic plasticity in conditional learning: the importance of spatiotemporal discontiguity - Schmitt, W; Arianpour, R; Deacon, R; Seeburg, P; Sprengel, R; Rawlins, J; Bannerman, D (Society for Neuroscience, 2004)
Gene-targeted mice lacking the AMPA receptor subunit glutamate receptor-A (GluR-A or GluR1) and mice with cytotoxic hippocampal lesions were compared with wild-type and sham-operated controls, respectively, on a conditional learning task using an elevated T-maze. Floor inserts (white perspex vs wire mesh) provided a conditional cue indicating in which goal arm a food reward was to be found. The relationship between the floor insert and the rewarded goal arm was constant throughout the experiment. Both lesioned and knock-out mice were able to acquire the task if the floor inserts extended throughout the entire maze, including the start arm and both goal arms. In contrast, both lesioned and knock-out mice were unable to acquire the task if the floor inserts were only present in the start arm of the maze. The absence of the conditional cue (the floor insert) at the time when the place-reward association was experienced thus critically determined whether or not the mice were impaired. We suggest that hippocampal GluR-A dependent synaptic plasticity contributes to a memory system in rodents for encoding both the spatial and temporal contexts (the where and the when) associated with a particular event.